2021
DOI: 10.1136/jitc-2021-002773
|View full text |Cite
|
Sign up to set email alerts
|

Metformin generates profound alterations in systemic and tumor immunity with associated antitumor effects

Abstract: BackgroundMetformin is a commonly used antidiabetic medication which has demonstrated promise as an anticancer agent alone and in combination with conventional treatment regimens. There is increasing evidence that metformin can also generate immunomodulatory effects in solid tumors and is currently being investigated as an adjunct to immune checkpoint inhibitors (ICIs). We hypothesized that metformin would generate a shift in immunity unfavorable to tumor growth and tested this hypothesis in a preclinical mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 54 publications
2
27
0
Order By: Relevance
“…We suspect metformin pretreatment not only impacts intracellular pathways to inhibit metastasis, but also modulates the extracellular microenvironment, e.g., adhesion molecules [ 48 ], vascular leakiness [ 49 ], and extracellular matrix remodeling [ 49 ] in distant organs. Of note, metformin also led to the activation of antitumor immune and metabolic reprogramming in both lab experiments and clinical trials [ 50 53 ]. Thus, metformin pretreatment reinforced these effects and showed fewer metastasis foci.…”
Section: Discussionmentioning
confidence: 99%
“…We suspect metformin pretreatment not only impacts intracellular pathways to inhibit metastasis, but also modulates the extracellular microenvironment, e.g., adhesion molecules [ 48 ], vascular leakiness [ 49 ], and extracellular matrix remodeling [ 49 ] in distant organs. Of note, metformin also led to the activation of antitumor immune and metabolic reprogramming in both lab experiments and clinical trials [ 50 53 ]. Thus, metformin pretreatment reinforced these effects and showed fewer metastasis foci.…”
Section: Discussionmentioning
confidence: 99%
“…Metformin administration induces interferon-gamma (IFN-γ) production in CD8+ tumor infiltrating lymphocytes in multiple solid tumor models [ 145 , 146 , 147 ]. Furthermore, metformin inhibited accumulation and suppressive activity of myeloid-derived suppressor cells, which are a major immunosuppressive cell type that inhibits T-cells and promotes tumor immune escape [ 145 , 148 ]. Interestingly, metformin is detrimental to CD19-chimeric antigen receptor-modified T cells as it inhibits proliferation and cytotoxicity while inducing apoptosis via AMPK activation and downstream suppression of mTOR [ 149 ].…”
Section: Metformin Mechanism Of Actionmentioning
confidence: 99%
“…The antitumor and immune effects of metformin are complex. Dosing and scheduling can have profound effects, and the challenges lie in determining optimal treatment regimens [ 158 ]. Furthermore, the impact of metformin on immune checkpoint protein expression should be further elucidated as studies have shown that metformin inhibits PD-L1 by endoplasmic reticulum-associated protein degradation in breast cancer cells [ 154 ].…”
Section: Clinical Perspective Of Immune Checkpoint Blockade Therapymentioning
confidence: 99%